(3COdI aj EKHGJ GdCgdIs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3CeG HYO abO hbY ai gPG GdTgQ hgh Ph GdMLI SfI KeGf hCQHYjf hSHY eGFg eSFdI JMJGL Edi GdfXQ ajgG s
(3BNQgG (B:s
(3Ke UGQ GdNHQ ef GdOjGQ GdeUQjI hLejY GdHdGO GdTGejg hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3jdjgG ahGFO hfbhd HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
Keywords: (3GdJhMjO hGdedd hGdfMds